Microorganisms on surface culture of injection port of IV sets and its implication to infection control - Gloria S. E. Coyoca; Verna S. A. Ardiente; Loida J. R. Beniga; Dennie Kate Pasco; Jessa M. O. Yuson (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Nosocomial infection is a disease caused by a pathogenic agent that is acquired during a patient’s hospitalization or treatment inside another health care facility. The said infection can be caused by microorganisms. These microorganisms may already be present in the patient's body or may come from the environment, contaminated hospital equipment; An intravenous (IV) set used during IV therapy is one example of the possible materials containing these microorganisms. The main purpose of this study is to determine the presence of microorganisms on injections ports of IV sets before and after disinfection whenadministering IV medications in the patients admitted to the medicine wards of Hospital X and Y. Presence of microorganisms despite disinfection may pose risk to patients through the entry of bacteria upon injection through the port. Thirty swab samples were obtained from each hospital. Swab samples were then isolated on nutrient agar plates. Hospital Y samples yielded no bacterial isolates whereas all 30 samples in Hospital X showed bacterial isolates. Swab samples underwent gram-staining to distinguish between gram-positive and gram-negative bacteria. Streptococcus species and Staphylococcus species which are classified as grampositive bacteria were among the bacterial species identified before and after disinfection and were found on all the samples obtained from Hospital X. Based on the findings of this study, adherence to infection controlprocedures were not well established to reduce or eliminate microorganisms on injection ports in Hospital X that may cause Nosocomial infections. In line with these, it is highly recommended that proper infection control and maintenance procedures should be strictly enforced to reduce, if not eliminate themicroorganisms on injection port which are possible causes of Nosocomial infections and may threaten thempatients’ health